WEBINAR dan WORKSHOP Front-End Fundamentals: A Beginner's Guide to Web Development for Junior Programmer - Kurniawan, Bagas; Zia Zhuang, Tan Kelvin; Jundullah, Khalid; Mujiastuti, Rully; Adharani, Yana; Sutrisno, Mirza (Institut Teknologi dan Bisnis Riau Pesisir, 2024)
Webinar dan workshop